Effects of Transfer Energy Capacitive and Resistive On Musculoskeletal Pain: A Systematic Review and Meta-Analysis : - Sadri, Soroush; Vahdatpour, Babak; Haghighat, Shila; Sadri, Leyli; Taghian, Mehdi (Galen Medical Journal, 2022)
The use of transfer energy capacitive and resistive (TECAR) therapy to treat musculoskeletal pain has not been clearly established. Hence, this study was conducted to combine the available results. We searched the main databases, including PubMed (January 1950), Web of Knowledge (January 1945), Scopus (January 1980), and ProQuest (January 1983) until December 2021, to find the related studies. Only those studies were included that assessed the pain in participants who received TECAR therapy and compared it with a control group. Using the random effect model, standardized mean difference (SMD) was calculated at a 95% confidence interval (CI). The differences between patients and control group were -1.04 after four weeks of intervention (95% CI: -1.59 to -0.48, I2=86.9%) and -1.80 after eight weeks (95% CI: -2.15 to -1.46, I2=87%), which was significant (P<0.001). The intra-group pain comparison before and after two, four, and eight weeks of TECAR therapy obtained SMD levels of -3.96 (95% CI: -5.28 to -2.65, I2=96.9%), -4.12 (95% CI: -5.98 to -2.26, I2=97.3), and -5.03 (95% CI: -7.23 to -2.83, I2=92.2%), respectively. Despite some limitations, our findings may assist clinicians in decision-making about TECAR therapy for the approach to musculoskeletal pain based on evidence-based medicine.